Menelaah Kembali Hadis-Hadis dalam Kitab Nasaih al-‘Ibad dan Sullam al-Munajah Karya Imam Nawawi Al-Bantani - Misbakhul Khaer; Amri Amri (Akademika: Jurnal Keagamaan dan Pendidikan, 2021)
Today, many hadiths with a weak status (ḍa`īf) or even false (mauḍū`) become the basis of worship. In addition, these two types of weak hadith are also still widely spread in some turats (yellow) books that are often studied in some pesantren. On this basis, the researcher is interested in studying the hadiths quoted by one of the eminent scholars of the archipelago, Sheikh Imam Nawāwī al-Bantanī, through some of his works, among them are the book Naṣā’iḥul `Ibād and Sullam al-Munājah. In connection with this, the researcher found that there are some hadiths with weak status, even isra`iliyat found in the book Naṣā’iḥul `Ibād. However, it has been known that this book is a genre of Sufism, most of its content leads to the study of morality and motivates pious deeds (fadha`ilul a’mal). So according to some scholars, a weak hadith that contains about fadha`ilul ‘amal can be practiced as long as it aims to motivate goodness and not in the realm of law, worship, and monotheism. In contrast to the other book, Sullam al-Munājah, whose content is more on jurisprudence, in this case, Imam Nawawi only quoted some of his authentic hadith. However, it would be good for a dai or khatib and also some pesantren to review the hadis that will be delivered, because the hadith are words and actions that are based on the noble figure of the Prophet Muhammad and become the second main source of Islamic law after the al-Qur’ān al-Karīm.